2019
DOI: 10.1128/jcm.01505-18
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Infections Due to Trichosporon : Species Distribution, Genotyping, and Antifungal Susceptibilities from a Multicenter Study in China

Abstract: A total of 133 clinical Trichosporon isolates were collected in the National China Hospital Invasive Fungal Surveillance Net (CHIF-NET) program in 2009 to 2016. Accurate identification was performed by sequencing of the intergenic spacer 1 (IGS1) region. Among these isolates, Trichosporon asahii (108 isolates [81.2%]) was the leading species, followed by Trichosporon dermatis (7 isolates [5.3%]), Trichosporon asteroides (5 isolates [3.8%]), Trichosporon inkin (5 isolates [3.8%]), Trichosporon dohaense (3 isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 39 publications
6
48
0
1
Order By: Relevance
“…We also found a high proportion of patient under 15 years (32.14%, 9/28) and a high mortality rate at three months (46.15%, 12/26). As reported in the literature, 12,14,32‐34 all T. asahii isolates were intrinsically resistant to flucytosine and less susceptible to fluconazole and amphotericin B while voriconazole had the most potent in vitro activity with MIC50 and MIC90 of 0.06 and 0.25 mg/L, respectively. Voriconazole is the treatment usually recommended for deep‐seated trichosporonosis 34 …”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We also found a high proportion of patient under 15 years (32.14%, 9/28) and a high mortality rate at three months (46.15%, 12/26). As reported in the literature, 12,14,32‐34 all T. asahii isolates were intrinsically resistant to flucytosine and less susceptible to fluconazole and amphotericin B while voriconazole had the most potent in vitro activity with MIC50 and MIC90 of 0.06 and 0.25 mg/L, respectively. Voriconazole is the treatment usually recommended for deep‐seated trichosporonosis 34 …”
Section: Discussionsupporting
confidence: 62%
“…This species is rarely involved in white piedra but is frequently recovered from patients with summer‐type hypersensitivity pneumonitis (SHP), an allergy developed after repeated inhalation of arthroconidia 8 . It is also isolated from immunocompromised patients and is the major Trichosporon species responsible for life‐threatening deep‐seated infection called trichosporonosis, 9‐13 mainly in patients with haematological malignancies 14‐16 . Fungaemia due to Trichosporon sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, different species of Trichosporon possess different drug sensitivities. For example, amphotericin B has a higher minimum inhibitory concentration (MIC) against T. asahii, T. faecale and T. coremiiforme, while T. inkin, T. ovoides, T. japonicum, T. domesticum, T. montevideense and T. cutaneum have lower MICs [46,[53][54][55][56]. Therefore, it is important to accurately analyse the epidemiological characteristics of different species of Trichosporon so the susceptibility and risk factors of infection can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In the review of Almeida Junior and Hennequin, they stated that there was no correlation between individual genotypes and sensitivities, but when combined the results of four different studies, they emphasized that VOR MIC values for genotype 3 strains were higher than genotype 1 strains, and this difference was statistically significant (1). Similarly, in the study of Guo et al (2019), the authors found that genotype 3 strains exhibited higher AMB MICs than did genotype 1 and 4 strains (7).…”
Section: Discussionmentioning
confidence: 99%